CORRELATION BETWEEN COORDINATION AND PERSONALITY TRAITS OF SOLDIERS IN BATTLE UNIT OF SLOVENIAN ARMED FORCES - Maja Pori; Primož Pori; Matej Tušak; Anja Valant Velepec (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The aim of the study was to investigate the correlation between motor ability of coordination and personality traits of Slovenian soldiers. The subject sample consisted of 94 soldiers in a battle unit of Slovenian Armed Forces (SAF) who were serving in the first brigade (age 26,5 ± 3,4 years). Motor ability of coordination was assessed with two motor tasks (polygon bac- kwards and figure 8 duck test). The structure of personality traits was measured with a FPI (Freiburg Personality Inventory) included 114 items and measured 9 personality traits of order I (neuroticism, impulsivity, depression, irritability, sociability, calmness, dominance, suppression, sincerity) and 3 personality traits of order II (extroversion, emotional istability, masculinity). The correlation between coordination and personality traits was estimated by the Pearson's correlation coefficient. The results show that soldiers who did worse in motor test polygon backwards were more neurotic, suppressed, and impulsive. They also tend to be more sociable. The correlation between second test of coordination shows that better soldiers in this test are more extrovert or less introvert.